2015
DOI: 10.1021/acs.nanolett.5b04033
|View full text |Cite
|
Sign up to set email alerts
|

Gold Nanoparticle-Decorated Scaffolds Promote Neuronal Differentiation and Maturation

Abstract: Engineered 3D neuronal networks are considered a promising approach for repairing the damaged spinal cord. However, the lack of a technological platform encouraging axonal elongation over branching may jeopardize the success of such treatment. To address this issue we have decorated gold nanoparticles on the surface of electrospun nanofiber scaffolds, characterized the composite material, and investigated their effect on the differentiation, maturation, and morphogenesis of primary neurons and on an immature n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
124
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 184 publications
(129 citation statements)
references
References 41 publications
4
124
1
Order By: Relevance
“…Recently Baranes et al reported a nerve guide fabricated with electrospun nanofibers doped with 10 nm Au NPs (shown schematically in Figure 2c). The scaffolds encouraged a longer outgrowth of the neurites in primary neurons of the medicinal leech, preferring axonal elongation over the formation of complex networks [27]. Similarly, Das and coworkers reported on a nerve guide fabricated by adsorbing Au NPs onto silk fibers.…”
Section: Peripheral Nerve Regenerationmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently Baranes et al reported a nerve guide fabricated with electrospun nanofibers doped with 10 nm Au NPs (shown schematically in Figure 2c). The scaffolds encouraged a longer outgrowth of the neurites in primary neurons of the medicinal leech, preferring axonal elongation over the formation of complex networks [27]. Similarly, Das and coworkers reported on a nerve guide fabricated by adsorbing Au NPs onto silk fibers.…”
Section: Peripheral Nerve Regenerationmentioning
confidence: 99%
“…( a ) Examples of epifluorescence images of NG108-15 neuronal cells cultured alone or with Au NRs and exposed to different laser irradiances, as indicated in each panel. Cells were marked for β-III tubulin (in red) and DAPI (in blue, reproduced with permission from [49]); ( b ) Spontaneous remyelination by Schwann cells (myelin marker P0, in red) was enhanced in mice treated with polyethylene glycol-coated Au NPs (reproduced with permission from [7]); ( c ) schematic representation of electrospun nanofibers doped with 10 nm Au NPs (reproduced with permission from [27]).…”
Section: Figurementioning
confidence: 99%
“…Poly(ethylene glycol) (PEG) coated on the surface of gold nanoparticles can promote recovery following SCI [Papastefanaki et al, 2015]. Gold nanoparticle-decorated tissue engineering scaffolds have been shown to promote increased axon extension of cultured neurons [Baranes et al, 2016]. The optical absorption of gold nanorods can be tuned in the visible to near-infrared range [Paviolo et al, 2013].…”
Section: Types Of Nanoparticles Utilized In the Spinal Cordmentioning
confidence: 99%
“…9,10 All these properties render AuNPs as a versatile nanoplatform for emerging biomedical applications in the design of biosensors, targeted drug delivery vehicles, photothermal therapy, and diagnostic bioimaging. 11 Recently, AuNPs have been extensively employed as emerging therapeutic agents for the treatment of AIDS, 12 Parkinson's disease, 13 and diabetes, 14 or controlling neural stem/progenitor cell renewal 15 and promoting osteogenic differentiation of mesenchymal stem cells. [16][17][18] Furthermore, AuNPs are also exploited as a novel class of antitumor agents in cancer therapy through inhibiting angiogenesis and ablating the tumor microvasculature, 19 enhancing chemosensitivity of cancer cells by reversing epithelial-mesenchymal transition, 20 preventing tumor growth and metastasis via abrogating growth factor signaling cascades, 21 and boosting the antitumor immune response as a vaccine platform.…”
Section: Introductionmentioning
confidence: 99%